Biaya Imbangan Eksternalitas Pabrik Gula Djombang Baru - Elly Septiana Dwi Kusuma; Purbowo; Umar Khasan (Journal of Economics Development Issues, 2023)
This study aims to analyze how many externalities are received by the community and determine the difference in income of the community during and after the milling process. This study uses the valuation method to estimate the costs and benefits of the existing impacts and the T-test to determine during and after the milling process in the “PG Djombang Baru” sugar factory, Jombang Regency, Indonesia. The results showed that the positive externality generated due to the activity of the “PG Djombang Baru” sugar factory was IDR 170.790.000 per year while the total cost borne by the community is IDR 2,144,640,000 per year with a total Externality Value of the “PG Djombang Baru” sugar factory of negative IDR 1,973,850,000 per year. So the costs incurred are more than the benefits received. Besides, the results of the T-test showed that there was no significant difference in income between during milling and after milling.